Multiscale Hierarchical Patterning by Sacrificial Layer‐Assisted Creep Lithography. Issue 17 (24th July 2019) - Jang, Segeun; Choi, Jiwoo; Shin, Minho; Yeon, Je Hyeon; Kim, Sang Moon; Choi, Mansoo
Abstract: The capability to fabricate various multiscale structures without limitations of size, morphology, and number of hierarchies via a simple process is highly desired in modern research. This work reports a powerful multiscale‐patterning method called sacrificial layer‐assisted creep lithography (SCL). Multiscale structures are successfully obtained by introducing a sacrificial layer, which has low creep compliance and preferential solubility in a nonpolar solvent, on a Nafion film during an additional creep‐based imprinting process. Through this method, deformation or geometrical loss of preformed structures and complex multiscale structures could be prevented including three‐level structures that are successfully constructed with well‐preserved nano/microstructures thanks to the sacrificial layer. To assess the diverse applicability of the SCL, a multiscale poly(dimethylsiloxane) channel with vertically crossed two‐groove structures is fabricated, and the directional switching of droplet spreading depending on the direction of the applied strain is demonstrated with the structure. Further, using multiscale pyramid structures, the overlapped optical properties of nano‐ and microstructures, which enhance overall reflectance of the surface, are verified. Abstract : A facile multiscale patterning method called sacrificial layer‐assisted creep lithography (SCL) is developed via creep deformation of Nafion and poly(methyl methacrylate) sacrificial layer. To assess the compressive creep behavior of the Nafion film, comprehensive experiments and simulations are conducted. A water guide poly(dimethylsiloxane) channel and multiscale TiO2 patterned layer are fabricated using SCL to examine some of its applications.